Harm reduction and drug policy: implications for South Africa - Rothfuchs, Steve (Institute of Criminology, 2026)
Psychoactive substances have been used for social or religious purposes around the globe for millennia. However, in modem times, their inherent properties and hazards have been exaggerated or misrepresented. They are illegal, even feared. Yet, the futility of eradication efforts exemplifies the fact that drugs are here to stay. There is no doubt that the abuse of these substances by a small percentage of users does result in significant damage. However, the standard prohibitory regimes compound the problem by treating the possession and use of these substances as a criminal rather than a health matter. Drugs and their users have been demonised and relegated to the fringes of mainstream society. Social reactionists provide a theoretical basis for this process in matters that often appear to have been tailored to their work. Harm reduction initially developed as a treatment perspective however its features also imply a much broader philosophy. Its central tenet is to diminish the damaging effects of substance use and it has, so far, been accepted in an unelaborated form in South Africa's National Drug Master Plan.